Hypervariable segment-! (HVS-I) Sequence Analysis Of Chinese Population of Peninsular Malaysia - Lee Loong, Chuen (PPSP, Universiti Sains Malaysia, 2007)
Throughout Malaysia history, most of the Peninsular Malaysian Chinese are known to be populated by those migrated from the China during the British colonial era (Barbie, 1992). The present study was undertaken to obtain information about the distribution of the existing HVS-1 sequence variations in the Chinese population of Peninsular Malaysia. A few studies have used RFLP analysis to characterize the mtDNA of Malaysian Chinese (Ismail, 2006; Mokhtaruddin, 2006; Ballinger et al., 1992). The primary purpose of this study is to provide HVS-1 sequence data by sequencing the HVS-1 of the 40 Chinese individuals from different parts of Peninsular Malaysia. The secondary purpose is classification of mtDNA haplogroup based on the HVS-1 sequence variation by alignment of samples sequence and Cambridge Reference Sequence (CRS) (Andrew et al., 1999). The samples were predicted to belong to the superhaplogroup M and haplogroup B in relatively high frequency as inferred from the study done by Ballinger et al., (1992). Analysis of HVS-1 within the control region (CR) of the mitochondrial genome revealed the presence of eight haplogroups: B, F, M, MC, MD, MG, N, and R. These haplogroups are the characteristics of Southeast Asian populations (Ballinger et al., 1992) and also found in significant proportion in Han Chinese of China (Y ao et al., 2002). Result shows that superhaplogroup M (includes MC, MD, and MG) is the most common haplogroup in the studied samples (55%), followed by haplogroup B (18%).